Effect of stirring on the properties of SILAR Cu-rich CuInS2films - Maheswari, B; Dhanam, M. (Photonics Letters of Poland, 2012)
CuInS2 (CIS) thin films are prepared by the successive ionic layer adsorption and reaction method (SILAR) by single cationic route under two different conditions (without stirring and with stirring). The effect of stirring on the structural, optical, compositional and morphological properties of the prepared Cu-rich CuInS2 thin films has been studied and reported in this paper. Full Text: PDF References M.Krunks, A.Mere, A.Katerski, V.Mikli and J.Krustok, "Characterization of sprayed CuInS2 films annealed in hydrogen sulfide atmosphere", Thin Solid Films 511-512, 434 (2006).CrossRef S.K.Kim, W.J.Jeong, G.C.Park, Y.G.Back, Y.G.Jeong and Y.T.Yoo, "Heat-treatment effect of chalcopyrite copper indium disulphide thin film growth", Synthetic Metals 71, 1747 (1995).CrossRef Roland Scheer, Progress in photovoltaics: Research and Applications, "Open questions after 20 years of CuInS2 research", (2012).CrossRef M.Krunks, O.Kijatkina, H.Renace, I.Oja, V.Mikli and A.Mere, "Composition of CuInS2 thin films prepared by spray pyrolysis", Thin Solid Films 403-404, 71 (2002).CrossRef Y.B.He, T.Kramer, I.Osterreicher, A.polity, R.Gregor, W. Krieg seis, D.Hasselkamp and B.K.Meyer, "Highly (112)-Oriented CuInS2 Thin Films Deposited by a One-Stage RF Reactive Sputtering Process", Jpn.J.Appl.Phys. 41, L484 (2002).CrossRef J.Qiu, Z.Jin, J.Qian, Y.Shi and W.Wu, "ILGAR CuInS2 films from various preparation conditions", Mater. Lett. 59, 2735 (2005).CrossRef N.Suriyanarayanan and C.Mahendran, "EDAX, SEM, Photoluminescence and Electrical properties of Zn- doped polycrystalline CuInS2 Thin films by spray pyrolysis", Archives of Physics Research 3 (1), 54 (2012).DirectLink Y.Pena, S.Lugo, M.C.Rodriguez, A.Vazquez, I.Gomez and P.Elizo nodo, "CuInS2 thin films obtained through the annealing of chemically deposited In2S3?CuS thin films", Appl.Surf. Sci. 257, 2193 (2011).CrossRef A.B.Mandale, S.D.Sathaye and K.R.Patil, "Preparation of Q-copper indium sulfide thin films by liquid?liquid interface reaction technique (LLIRT)", Mater. Lett. 55, 30 (2002).CrossRef M.Ben Rabeh, N.Chaglabou and M.Kanzari, "Effect of Antimony Incorporation in CuInS2 Thin Films", Chalcogenide Lett. 6 (4),155 (2009).CrossRef Y.B.He, A.Polity, R.Gregor, D.Pfisterer, I.Osterreicher, D.Hasse lkamp and B.K.Meyer, "Characterization of RF reactively sputtered Cu?In?S thin films", Physics B. 308-310, 1074 (2001).CrossRef K.Zeaiter, Y.Llinares and C.Llinares, "Structural and photoluminescence study of the quaternary alloys system CuIn(SxSe1?x)2", Sol. Energy Mater. Sol. Cells 61, 313 (2000).CrossRef A.Antony, A.S.Asha, R.Yoosuf, R.Manoj and M.K.Jayaraj, "Growth of CuInS2 thin films by sulphurisation of Cu?In alloys", Sol. Energy Mater. Sol. Cells 81, 407 (2004)CrossRef Y.Shi, Z.Jin, C.Li, H.An and J.Qiu, "Effect of [Cu]/[In] ratio on properties of CuInS2 thin films prepared by successive ionic layer absorption and reaction method", Appl. Surf. Sci. 252, 3737 (2006).CrossRef S.J.Roh, R.SMane, H.Pathan, O.S.Joo and S.H.Han, "Rapid growth of nanocrystalline CuInS2 thin films in alkaline medium at room temperature", Appl. Surf. Sci. 252, 1981 (2005).CrossRef Gray Hodes, Chemical Solution Deposition of Semiconductor Films (Marcel Dekker, Inc, pp-131).DirectLink R.P.Wijesundera and W.Siripala, "Preparation of CuInS2 thin films by electrodeposition and sulphurisation for applications in solar cells", Sol. Energy Mater. Sol. Cells 81, 147 (2004).CrossRef C.Guillen, J.Herrero, M.T.Gutierrez and F.Briones, "Structure, morphology and optical properties of CuInS2 thin films prepared by modulated flux deposition", Thin solid films 480- 481, 19 (2005). <a href="http://pdn.sciencedirect.com/science?_ob=MiamiImageURL&_cid=271603&_user=3029679&_pii=S0040609004015810&_check=y&_origin=article&_zone=toolbar&_coverDate=01-Jun-2005&view=c&originContentFamily=serial&wchp=dGLzVlV-zSkzS&md5=7ce420f1237671a62780e2def7d719fb&pid=1-s2.0-S0040609004015810-main.pdf">DirectLink P.Guha, S.Gorai, D.Ganguli and S.Chanudhuri, "Ammonia-mediated wet chemical synthesis of CuInS2"Mater. Lett. 57, 1786 (2003).CrossRef Y.B.He. T.Kramer, I.Osterreicher, A.Polity, B.K.Meyer and M.Hardt, "Post-growth treatment effects on properties of CuInS2 thin films deposited by RF reactive sputtering", Semicond. Sci.Technol. 20, 685 (2005).CrossRef S.Aksay and B.Altiokka, "Effect of substrate temperature on some of the optical parameters of CuInS2 films", Physica Status Solidi (c) 4, 585-588, No.2 (2007)CrossRef N.M.Ravindra, Preethi Ganapathy, Jinsoo Choi, "Energy gap?refractive index relations in semiconductors ? An overview", Infrared Physics and Technology, 50, 1 21 (2007)CrossRef